Grammar of Difference. General Education in the Netherlands and Java, 1800-1940 - Elise van Nederveen Meerkerk (Historical Life Course Studies)
This contribution compares developments in school enrolment and public investments in primary education in the Netherlands and its most important colony in the 19th century: the Netherlands East Indies, more specifically the island of Java. Despite being part of the same Empire, conditions in both regions were very different, with the metropole having already quite high enrolment rates from the beginning of the period studied (the early 19th century) compared to very low school attendance in the colony. For long, the colonial government left indigenous education in Java to religious and private initiatives, whereas primary schooling in the Netherlands was increasingly financed and regulated. Rising interest for public schooling in the colony, including some government investment in the first decades of the 20th century did lead to some changes, but these were insufficient to prevent Dutch and Javanese children from experiencing a fundamentally different educational upbringing.